Jumlah Rapat Komite Audit, Jumlah Dewan Direksi, dan Jumlah Dewan Komisaris terhadap Pengaruh Penerapan GCG pada Perusahaan Sektor Garmen dan Tekstil yang Terdaftar di Bursa Efek Indonesia (BEI) pada Tahun 2020-2021 - Raissa Amelia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to investigate the influence of the implementation of Good Corporate Governance (GCG), the number of audit committee meetings, the number of board of directors, and the number of board of commissioners on the financial performance of companies in the garment and textile sector listed on the Indonesia Stock Exchange (BEI) in the years 2020-2021. The indicators of GCG implementation are proxied by commitment, transparency, accountability, independence, responsibility, fairness, leadership, and vision-mission. Furthermore, financial performance is measured using Return on Assets (ROA). The research employs T and F statistical tests as the research methods. Based on the findings, it is revealed that the implementation of GCG, the number of audit committee meetings, the number of board of directors, and the number of board of commissioners, either partially or simultaneously, do not have a significant effect on the financial performance of companies in the garment and textile sector listed on the Indonesia Stock Exchange (BEI) in the years 2020-2021.